Is informal transport flexible? - Tamara Kerzhner (Journal of Transport and Land Use)
Informal transport is often described as flexible, reactive, demand responsive, niche-filling, and in-tune with passenger needs. This paper proposes expanded definitions of flexibility in the operations of informal transport networks and presents a theoretical framing for understanding the growth and change in the locations of routes and terminals. Based on surveys and interviews of transport workers and regulators in four African cities, it argues that individually competing vehicles encounter coordination failures that limit their incentives for searching out niche services. Meanwhile, in cities with localized, route-based associations, organizations of multiple vehicles are able to take on the initiative and risk of developing new service locations and responding to passenger demand. This is done through a complex, gradual process that includes temporary subsidies to drivers and operators, testing and measuring potential demand, and advertising the new route. The key mechanism is in competition not between individual drivers, who manage internal competition carefully with a variety of mechanisms to distribute income opportunities fairly, but between firms and associations over territorial coverage. This not only opens potential for engaging transport associations in planning and policymaking, but also reveals limitations to the coverage and equity of access offered by existing networks and incentive structures.